Identification and Analysis of Dysfunctional Genes and Pathways in CD8+ T Cells of Non-Small Cell Lung Cancer Based on RNA Sequencing - Tao, Xuefang; Wu, Xiaotang; Huang, Tao; Mu, Deguang (Frontiers in Genetics, 2020)
Lung cancer, the most common of malignant tumors, are typically of the non-small cell (NSCLC) type. T-cell based immunotherapies are a promising and powerful approach to treating NSCLCs. To characterize the CD8+ T cells of non-small cell lung cancer, we re-analyzed the published RNA-Seq gene expression profiles of 36 CD8+ T cell isolated from tumor (TIL) samples and 32 adjacent uninvolved lung (NTIL) samples. With an advanced Monte-Carlo method of feature selection, we identified the CD8+ TIL specific expression patterns. These patterns revealed the key dysfunctional genes and pathways in CD8+ TIL and shed light on the molecular mechanisms of immunity and use of immunotherapy.